Variación espacio-temporal en la dieta del coyote en la costa norte de Jalisco, México - Guerrero, Sergio; Badii, Mohammad H.; Zalapa, Silvia S; Arce, Juan A. (Instituto de Ecología, A.C., 2020)
The present work analized the changes at local level in the food habits of coyote. This work was developed in a Tropical Subdeciduos Forest in the North Coast of Jalisco State. We collected scats from March 1999 to April2001, in four sites with different conditions. The scats were analized annually, seasonally (dry-wet), for the whole area and between sites. In general, the vegetal items (44.20%), and mammals (36.05%) reached 80% of relativefrecuency of ocurrence in the diet, observed significant changes between seasons in both groups. The elements with highest relative frequency of occurrence were Vitex hemsleyi, Sigmodon mascotensis and Liomys pictus. The relative frequency of ocurrence of vegetal items were different between sites, with highest values in site 1 (47.35%), and the lowest in site 3 (22.22%); the highest frequencies of mammals were in the site 4(44.83%) and the lowestin the site 2 (30.77%). Seasonally, vegetal items consumption were different in the site 2 and site 4, mammals were different in the site 2 and site 4, birds in the site 4, and insects in the site 1. Diversity of items, mesured with indexof Shannon (H'), value obtained in the diet of coyote H'= 2.33; diversity of items between sites and seasons were different too. We concludes that the opportunistic behavior of the coyote prevails at local level, showing widecapacity of adaptation in order to use the availability and abundance of feeding resources.